2014
DOI: 10.1007/s10404-014-1514-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetically driven deterministic lateral displacement for particle separation in microfluidic devices

Abstract: An electrokinetically-driven deterministic lateral displacement (e-DLD) device is proposed for the continuous, two-dimensional fractionation of suspensions in microfluidic platforms. The suspended species are driven through an array of regularly spaced cylindrical posts by applying an electric field across the device. We explore the entire range of orientations of the driving field with respect to the array of obstacles and show that, at specific forcing-angles, particles of different size migrate in different… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…In previous work, we showed that DLD could also be operated as an active method using external forces to drive the separation. In particular, we demonstrated the use of both gravity and electrokinetic flow to separate suspended particles in microfluidic DLD systems (Devendra and Drazer 2012;Hanasoge et al 2014). We also showed that both driving fields lead to transport and fractionation analogous to the flow-driven case, and in excellent agreement with our previous studies performed in scaled-up versions of microfluidic systems (Balvin et al 2009;Bowman et al 2012;Bowman et al 2013).…”
Section: Deterministic Lateral Displacement Separation Systemssupporting
confidence: 86%
“…In previous work, we showed that DLD could also be operated as an active method using external forces to drive the separation. In particular, we demonstrated the use of both gravity and electrokinetic flow to separate suspended particles in microfluidic DLD systems (Devendra and Drazer 2012;Hanasoge et al 2014). We also showed that both driving fields lead to transport and fractionation analogous to the flow-driven case, and in excellent agreement with our previous studies performed in scaled-up versions of microfluidic systems (Balvin et al 2009;Bowman et al 2012;Bowman et al 2013).…”
Section: Deterministic Lateral Displacement Separation Systemssupporting
confidence: 86%
“…Examples include the study of the transport of colloidal particles through arrays of micro-scale potential landscapes in the HOT generated potential wells [1][2][3][4][5][6] , investigation of transport and separation of overdamped particles in a microfluidic system 7 , sorting of chiral particles exploiting lattice potentials 8 , dynamic ordering and locking states of colloidal monolayers on a decagonal quasiperiodic surface 9 , sortings of particles within a microfluidic chip using a dual-channel line optical tweezers with a 'Y' shape channel 10 and, experimental investigation for the transport of 100 and 500 nm plasmonic nanoparticles in a two-dimensional optical lattice 11 . An array of obstacles on a surface is another technique for separating mesoscale particles [12][13][14][15][16][17][18][19][20][21][22][23] . In both cases, sorting occurs based on the fact that because of the potential wells (obstacles), particles' path deviates from the direction of the external force (fluid flow).…”
mentioning
confidence: 99%
“…In addition to size separation, DLD has been successfully applied in microfluidic systems to separate species with different shapes and deformability 6 7 8 9 10 . It was originally proposed as a flow driven, passive separation method but we have recently shown that active , force-driven DLD (f-DLD) is also effective in separating species by size 11 12 13 and shape 10 . In the majority of DLD systems the obstacle array is a periodic arrangement of cylindrical posts, but other obstacle shapes have been studied to enhance performance 14 or to separate non-spherical particles 9 .…”
mentioning
confidence: 99%
“…In all cases, however, the separation in DLD devices has been exclusively based on the motion of the suspended particles in the basal plane of the array. As a result, and in spite of many variations 9 11 12 14 , DLD systems have been limited to binary fractionations, in which the sample stream is split into two fractions. Then, to separate a polydisperse suspension into its individual components it is necessary to use multiple DLD systems in series or a single system in which the geometry/orientation of the array changes (continuously) in the direction of the flow 1 15 16 17 .…”
mentioning
confidence: 99%